Evaluation of pulpal anesthesia and injection pain using IANB with pre-heated, buffered and conventional 2% lignocaine in teeth with symptomatic irreversible pulpitis—a randomized clinical study - Gandhi, Namita; Shah, Nimisha; Wahjuningrum, Dian Agustin; Purnomo, Sweetly; Nooshian, Riana; Arora, Suraj; Pawar, Ajinkya M. (PeerJ, 2022)
Background The efficacy of 2% lignocaine is reduced in a hot tooth. Local aesthetic agents can be preheated and buffered to increase their effectiveness. The present investigation was carried out due to limited information concerning adult patients with symptomatic irreversible pulpitis in mandibular teeth. Methods A total of 252 individuals were included in the clinical trial in accordance with the selection criteria only after clinical study was registered with the Clinical Trial Registry of India (CTRI/2020/09/027796). Scores on the visual analog scale (VAS) and electric pulp test (EPT) on a 1–10 scale were recorded prior to the commencement of therapy. In this double-blinded study, patients were randomly divided by a co-investigator using computer randomisation (www.randomizer.org) into three groups, group A: inferior alveolar nerve blocks (IANB) with 2% lignocaine preheated at 42 °C (injected at 37 °C) (N = 84), group B: IANB of 2% lignocaine buffered with 0.18 ml of 8.4% sodium bicarbonate (N = 80) and group C: 2% lignocaine (N = 88). Excluding the dropouts of individuals (n = 11), wherein the anaesthesia failed, a total of 241 people were finally assessed 15 minutes after profound anaesthesia, endodontic access, and intraoperative pain were quantified using VAS. Pain on injection for all three groups was recorded immediately after IANB with VAS. The analysis was performed using one way ANOVA with Tukey’s post hoc test and Paired T-Test using SPSS version 21. Results Preheated, Buffered, and conventional 2% lignocaine showed statistically significant reduction in intraoperative pain (P < 0.001) compared to pre-operative but on inter-group comparison preheated and buffered showed highly significant pain reduction compared with conventional 2% lignocaine (P < 0.001). Conclusions Warm and buffered local anaesthetic (LA) were effective in reducing intraoperative discomfort than conventional LA. Preheated local anesthetics caused the least pain, followed by buffered local anesthetics, while conventional local anesthetics caused the most pain.
Keywords: Buffered; Local anesthesia; Pre-warm; Irreversible pulpitis; Endodontics